PERAN PATROLI SATUAN SABHARA DALAM UPAYA PENCEGAHAN PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLRES GARUT - Siahaya, Pierre Novian (Police Studies Review, 2017)
Motorcycle theft has become one of the biggest problems in Garut Regency which has caused anxiety and insecurity in the population. Garut Regional Police has made an attempt to provide security and peace for the society, by doing preventive action such as doing patrol carried out by the Sabhara unit. The goal is to prevent motorcyle theft. Based on data of Garut Regional Criminal Investigation Police, the number of motorcycle theft has significantly increased. The objective of this research is to know how the Sabhara unit in substance operate and the attempt of preventing crime of motorcycle theft in Garut Regency. This research has used qualitative methode, with analyses descriptive type which is intended to be able to give detailed and actual informations, and to able to describe the symptomps, problems and the condition around Garut Regency so that this could help to evaluate in making programmes, plans and decision in the near future. This study refers to Article 28 section (2) and has been regulated in Article 28 section (1) Kabaharkam Regulation Number 1 Year 2017 dated February 16, 2017 which can be used as a reference in making Operational Standards Procedures created by the highest leadership, namely the Police Chief. By doing this study, writer can now analyse with some theories and concepts such as Iceberg Theory where in the fundamental substance shows that the Garut Regency Police Sabhara unit has not yet done the preventive activities for motorcycle theft in Garut Regency. Afterward with the management theory we can learn that the patrol activity is not yet done correctly and in tools of management concept we learn that men that haven't been trained formally yet also became one of the factors of obstacle. Results of this study are to teach and give advice of what could be done better in the future such as how to use time effectively, adjusting places and how to coordinate well between Sabhara unit officer and the people or society in Garut Regency during the patrol activity. And how to collaborate with the Binmas Unit in order to provide a symbol or counseling to the community surrounding about motorcycle theft. Furthermore is about how to optimize reporting through social media to monitor and check the implementation of Patrol. Keyword :Crime Prevention, Patrol Unit, Motorcycle Theft.